SPATIAL DISTRIBUTION OF TOPONYMY IN KARST AREAS GIRITONTRO - Pipit Wijayanti; Baiq Liana Widiyanti; Rita Noviani; Baiq Rismarini Nursaly (Universitas Sebelas Maret (UNS), 2024)
Every object in the form of an earth element or man-made feature has a name with various origins. The origins of place names can be categorized based on geography, history, folklore/culture and language so that their spatial distribution can be known. This research explores the spatial distribution of the origins of naming earth elements and man-made features in the Giritontro District. The study begins by identifying the aspects of the earth's appearance and man-made features and then finding the meaning of naming each identified element. Data collection was carried out using in-depth interviews. Determining the sources used the snowball sampling method. The results of the research show that the toponymically identified objects are dominated by man-made features with a spatial distribution of 92% in Giritontro Village, 72% in Pucanganom Village, 52% in Tlogosari Village and 78% in Jatirejo Village. The remainder is dominated by the earth's elements of the Karst Area, such as caves, hills, and springs, with a spatial distribution of Bayemharjo Village at 63%, Ngargojarjo at 53% and Tlogoharjo Village at 66%. Meanwhile, the spatial distribution of toponymy in Giritontro District, whose origin is dominated by language, is known to be spread across Giritontro District with a percentage of 60%. Apart from that, the toponymy found was predominantly geographically dispersed across Pucanganom Village with a portion of 40%, Tlogosari Village at 60%, Jatirejo Village at 61%, Bayemharjo Village at 61%, Ngargoharjo Village at 57% and Tlogoharjo Village 46%. The geographical conditions referred to are those attached to the object or the object's proximity to geographical things (associations) which are dominant in the Karst Area.